Fast and easy detection of CMY-2 in Escherichia coli by direct MALDI-TOF mass spectrometry - Figueroa Espinosa, Roque Arnulfo (2018)
Fast typing methods for third generation cephalosporin resistance mechanisms are needed to guide appropriate treatment and prevent potential dissemination events. In this study we used a novel short and fast methodology for the identification of CMY-2 in 50 well characterized clinical isolates of E. coli by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry- MALDI-TOF MS. Samples were prepared using the double layer sinapinic acid technique for detection of intact proteins Comparison among mass spectral profile of different strains between m/z 35,000–45,000 Da showed that two groups of isolates could be differentiated after peak analysis. A single distinctive peak with different intensities, at approximately m/z 39,800 Da was found in all CMY-2 producing strains (transconjugant, transformant and wild type) and consistently absent in the control groups (ESBL producers and susceptible strains). Statistical results showed 100% values for sensitivity and specificity, indicating a perfect test and a high discriminative power. In this study, we demonstrated that MALDI-TOF MS has the potential to detect directly the most clinically relevant acquired AmpC β-lactamase, the CMY-2-enzyme, in E. coli with a less time-consuming process as compared to conventional methods. Our results may constitute the basis for further research to detect other β-lactamases, or even other resistance markers.